Answer:
y = 2*x^2 - 2*x - 24
Step-by-step explanation:
If we have a quadratic function with roots a and b, we can write the equation for that function as:
y = f(x) = A*(x - a)*(x - b)
Where A is the leading coefficient.
In this case, we know that the roots are: 4 and -3
Then the function will be something like:
f(x) = A*(x - 4)*(x - (-3) )
f(x) = A*(x - 4)*(x + 3)
Now we need to determine the value of A.
We also know that the graph of the function passes through the point (3, -12)
This means that:
f(3) = -12
Then:
-12 = A*(3 - 4)*(3 + 3)
-12 = A*(-1)*(6)
-12 = A*(-6)
-12/-6 = A
2 = A
Then the equation is:
y = f(x) = 2*(x - 4)*(x + 3)
Now we need to write this in standard form, so we just need to expand the equation:
y = f(x) = 2*(x^2 + x*3 - x*4 - 4*3)
y = f(x) = 2*(x^2 - x - 12)
y = f(x) = 2*x^2 - 2*x - 24
Then the relation is:
y = 2*x^2 - 2*x - 24
Answer: Hm,.
Step-by-step explanation:
If you need all of these, here is this.
Fraction: 5/100
Decimal: 0.05
Percent: 5%
Answer:
i think it 37 square feet